2005
DOI: 10.1038/sj.onc.1208909
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Rac1 and Rac3 GTPases in human tumor cell invasion

Abstract: Members of the Rho family of small GTPases have been shown to be involved in tumorigenesis and metastasis. Currently, most of the available information on the function of Rho proteins in malignant transformation is based on the use of dominant-negative mutants of these GTPases. The specificity of these dominant-negative mutants is limited however. In this study, we used small interfering RNA directed against either Rac1 or Rac3 to reduce their expression specifically. In line with observations using dominant-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
206
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 225 publications
(223 citation statements)
references
References 47 publications
14
206
3
Order By: Relevance
“…Rac3 has been reported to be involved in the invasion of glioblastoma cells, but its function remains unknown (Chan et al, 2005). The involvement of Rac3 in cellsubstrate adhesion during cell invasion is a novel finding in this study.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Rac3 has been reported to be involved in the invasion of glioblastoma cells, but its function remains unknown (Chan et al, 2005). The involvement of Rac3 in cellsubstrate adhesion during cell invasion is a novel finding in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Inhibition of Rac signaling by the expression of Rac1 T17N in U87MG cells changed the morphology of the cells from elongated to round (Figures 3e and f). It has been reported that Rac1 and Rac3 play pivotal roles in the invasive process of glioblastoma cells (Chan et al, 2005); thus, the expression of Rac1 and Rac3 was repressed by RNAi in U87MG cells (Figure 3a). As we did not have an antibody specific for Rac3, the effect of Rac3-directed siRNA (Rac3-RNAi) on protein expression was confirmed using an antibody that recognizes both Rac1 and Rac3.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The Cdc42 siRNA oligo was: 5′-AAAGACTCCTTTCTTGCTTGT-3′. MTLn3 cells were transfected with 100nM Rac or Cdc42 siRNA or with control siRNA sequences targeting GL2 luciferase [28] (Ambion) for 48 hours prior to the day of the experiment using Oligofectamine (Invitrogen) as described by the manufacturer. Rac and Cdc42 suppression of protein levels was analyzed by Western blotting using antibodies against total Rac and Cdc42 respectively.…”
Section: Cell Transfection With Small Interfering Rnamentioning
confidence: 99%
“…The time interval between successive frames was 1 min. Motility parameters were calculated using DIAS software [28], and the data are the mean ± SEM from 15-40 cells per condition.…”
Section: Supplementary Materialsmentioning
confidence: 99%